ψ(2S) production and nuclear modification factor in nucleus–nucleus collisions with ALICE - Hushnud H. (EPJ Web of Conferences, 2023)
Charmonium production is sensitive to deconfinement in nucleusnucleus collisions. The production via regeneration within the QGP or at the phase boundary has been identified as an important ingredient for the description of the centrality and transverse momentum dependence (pT) of the J/ψ nuclear modification factor (RAA) at the LHC. ψ(2S) production relative to J/ψ is one possible discriminator between the two different regeneration scenarios. At the LHC. there is so far no significant observation of the ψ(2S) in central nucleus-nucleus collisions at low-pT, where regeneration is expected to play an important role. The combined Run 2 data set of ALICE allows one to extract a significant ψ(2S) signal in this kinematic region at forward rapidity, in the dimuon decay channel. In this contribution, we present for the first time results on the ψ(2S)-to-J/ψ single ratio and double ratio (to pp collisions) as well as the ψ(2S) nuclear modification factor, in Pb-Pb collisions at √SNN = 5.02 TeVsNN=5.02 TeV. The ψ(2S)-to-J/ψ double ratio and ψ(2S) RAA are calculated using a new proton-proton reference with improved precision. Results are compared with model calculations.